PEMANFAATAN WEB SISTEM INFORMASI AKADEMIK SEBAGAI PENGONTROL NILAI SISWA (STUDI KASUS) MTS PONDOK MODERN AL-ISLAM NGANJUK - HARYANI HARYANI (Paradigma, 2015)
Information Technology in education is now widely used by academics. example is the development of web-based information systems academic. Information technology has a significant role in information services to the public related to academic information. Therefore the implementation of a web-based academic information system at the junior secondary school Nganjuk Al-Islam is certainly right to say so.Designing Web-based information systems academic aims to provide academic information. In designing the system this information is not only needed in the form of information system model so, but there are several stages in the design of these systems include the planning, analysis phase, the design phase and the implementation phase.The results of the design of web-based information systems academic is expected to help academic performance in providing academic information services. This system will give the students' progress reports such as report cards and the value of UTS / UAS online. Besides, parents can also monitor the progress of student learning outcomes.